2021
DOI: 10.3389/fimmu.2021.721048
|View full text |Cite
|
Sign up to set email alerts
|

Aquaculture Reuse Water, Genetic Line, and Vaccination Affect Rainbow Trout (Oncorhynchus mykiss) Disease Susceptibility and Infection Dynamics

Abstract: Infectious hematopoietic necrosis virus (IHNV) and Flavobacterium psychrophilum are major pathogens of farmed rainbow trout. Improved control strategies are desired but the influence of on-farm environmental factors that lead to disease outbreaks remain poorly understood. Water reuse is an important environmental factor affecting disease. Prior studies have established a replicated outdoor-tank system capable of varying the exposure to reuse water by controlling water flow from commercial trout production race… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The detection of F. psychrophilum in only this sample may indicate that a coinfection was occurring within this raceway, but diagnosis was not undertaken as an infection cause was already established. A previous study at this farm site (but not at the hatchery facility) identified F. psychrophilum on sampled fish at a high frequency using qPCR (39). The lack of F. psychrophilum-positive samples in our dataset may be at least partly due to the reduced sensitivity of MiSeq sequencing for pathogen detection compared to traditional qPCR methods (23).…”
Section: Discussionmentioning
confidence: 76%
“…The detection of F. psychrophilum in only this sample may indicate that a coinfection was occurring within this raceway, but diagnosis was not undertaken as an infection cause was already established. A previous study at this farm site (but not at the hatchery facility) identified F. psychrophilum on sampled fish at a high frequency using qPCR (39). The lack of F. psychrophilum-positive samples in our dataset may be at least partly due to the reduced sensitivity of MiSeq sequencing for pathogen detection compared to traditional qPCR methods (23).…”
Section: Discussionmentioning
confidence: 76%
“…Our results suggest that both neuropeptides induce the expression of proinflammatory cytokines, while VIP1 further modulates the anti-inflammatory response. Finally, rainbow trout have been described as susceptible to infection by aquatic pathogens such as Piscirickettsia salmonis [ 52 ], as well as opportunistic pathogens such as Aeromonas hydrophila , Pseudomonas fluorescens and Yersernia ruckeri [ [53] , [54] , [55] ]. Prophylactic and therapeutic strategies are limited, so these infections lead to production losses at the industrial level, which can also have environmental consequences such as antibiotic resistance [ 52 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Everson et al. ( 156 ) showed the importance of environmental factors, host genetics, and vaccination in relation to infection and mortality related to infectious diseases. However, the main reason would be related to insufficient and/or transient activation of the CMI response induced by conventional vaccines ( 1 , 10 13 , 25 , 29 , 38 , 97 , 105 ).…”
Section: Vaccination Against P Salmonis : Mission ...mentioning
confidence: 99%